Construction of an electric microenvironment in piezoelectric scaffolds fabricated by selective laser sintering. Issue 16 (November 2019) - Shuai, Cijun; Liu, Guofeng; Yang, Youwen; Qi, Fangwei; Peng, Shuping; Yang, Wenjing; Liu, Zheng
Abstract: It is well established that the electric microenvironment plays a vital role in promoting bone regeneration and repair. In this work, a BaTiO3 polymer scaffold was fabricated by selective laser sintering to overcome the challenges in manufacturing a 3D porous structure. More significantly, the orderly orientated dipoles of poled BaTiO3 deflect when a force is applied to the scaffolds, which results in a large number of charges generated on the scaffolds. The results indicated that the poled scaffold with 20 wt% BaTiO3 presented the highest electrical output performances under the same external force. The electric cues efficiently enhanced the cell viability, adhesion and proliferation under the action of ultrasound. Simultaneously, the tensile strength and modulus were significantly increased by 61.3% and 34.9%, respectively, which were attributed to the fact that crack propagation was prevented by BaTiO3 nanoparticles. All of these positive results demonstrated that 3D piezoelectric scaffolds present great potential in bone regeneration.